1988
DOI: 10.1002/rcm.1290021111
|View full text |Cite
|
Sign up to set email alerts
|

The determination of protein, oligonucleotide and peptide molecular weights by ion‐spray mass spectrometry

Abstract: The mass spectra of several compounds with molecular weights in the 2500-20,000 Da range were obtained with a quadrupole mass spectrometer equipped with an atmospheric pressure ion source. Average molecular weight determinations of mellitin (2846.4 Da), a synthetic oligonucleotide (4262.8 Da), myoglobin (16,950.4 Da) and on the subunits of beta-lactoglobulin (18,277.1 Da) requiring as little as 1 pmol of material were achieved with accuracies and precisions of +/- 1 Da. An ion-spray interface was used to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
286
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(294 citation statements)
references
References 10 publications
7
286
0
1
Order By: Relevance
“…Covey et al [27] found that the total number of basic residues (arginine, histidine, lysine, and the N-terminus) was often similar to the maximum charge state of a protein. Smith et al [4] also provided supporting details for this concept by compiling a list of proteins and peptides by including the maximum charge state obtained from ESI spectra and the number of basic sites.…”
Section: Methodsmentioning
confidence: 99%
“…Covey et al [27] found that the total number of basic residues (arginine, histidine, lysine, and the N-terminus) was often similar to the maximum charge state of a protein. Smith et al [4] also provided supporting details for this concept by compiling a list of proteins and peptides by including the maximum charge state obtained from ESI spectra and the number of basic sites.…”
Section: Methodsmentioning
confidence: 99%
“…The average molecular mass of the glycopeptide (or peptide) can be calculated from the spectra based on the observed masses for more than one defined charge state of the molecule (Covey et al, 1988;Fenn et al, 1989). For example, Figure 3B reveals peaks at m/z 1,073.9 and m/z 1,610.1.…”
Section: Selective Detecfion Of Glycopeptidesmentioning
confidence: 99%
“…Several factors have been shown to influence the observed charge state distribution, including molecular conformation [4][5][6], acid-base chemistry both in solution and in the gas phase [7][8][9][10][11], solvent composition [8], instrumental factors, etc. Several models have been proposed to qualitatively account for some of these effects [12][13][14][15]. A general conclusion from several studies is that the electrospray charge state distributions of proteins formed from denaturing solution conditions are shifted to higher charge states (lower m/z) than those formed from solutions in which the protein has significant tertiary structure.…”
Section: Introductionmentioning
confidence: 99%